Pektus - Quesada, Isabel Maria Luz Mangay 1994-; Quesada, Isabel Maria Luz Mangay; Campos, Patrick F.; University of the Philippines Diliman. College of Mass Communication (2015)
"Pektus tells the story of a day in the lives of two ordinary men in the city - both proud, indifferent, and bound by the confines of their milieu and their choices in life- and their incidental yet preordained meeting in a one-way alley that would change their lives thereafter. Raising questions of how far people have control over what happens in their lives, the films seeks to explore the complex matters of circumstance versus choice, breaking points, second chances, and ideas concerning the determined, free will and self-determinism."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Free will and determinism